Antifungal and antibacterial properties of three medicinal plants from Malaysia - Pei Shing, Gwee; Li Wen, Chen; Syu Wei, Tan; Hean Chooi, Ong; Soo, Khoo Kong; Weng, Sit Nam (Pharmacognosy Communications)
Introduction: The increase of opportunistic fungal infections and the escalation of bacterial resistance have seriously reduced the efficacy of chemotherapeutic agents available. Thus the search for new antimicrobial agents from natural sources such as medicinal plants becomes necessary. Methods: The aerial parts of Diplazium esculentum and Sechium edule, and the fruits of Solanum muricatum were used, and extracted sequentially using hexane, chloroform, ethyl acetate, ethanol, methanol, and water. The extracts were then evaluated, in triplicate, against a panel of 12 medically-important microorganisms for microbiostatic and microbiocidal activities using colorimetric broth microdilution methods. Results: The total percentage yield obtained were 1.20%, 1.84% and 3.53% (w/w, based on fresh weight) for D. esculentum, S. edule and S. muricatum, respectively. All plant extracts showed antifungal activity with 66% and 49% of the bioassays demonstrating fungistatic and fungicidal activity, respectively. Two yeasts, Cryptococcus neoformans and Issatchenkia orientalis were found to be susceptible to all extracts. The lowest minimum inhibitory concentration (MIC) and minimum fungicidal concentration (MFC) was exhibited by the hexane extracts of S. edule and S. muricatum against C. neoformans, both with values of 0.08 mg/mL. In the antibacterial screening assays, 49% of the bioassays exhibited bacteriostatic activity while only 21% of them showed bactericidal activity. The lowest MIC and minimum bactericidal concentration (MBC) was recorded for the hexane extract of S. muricatum against Bacillus cereus and Klebsiella pneumoniae, both with values of 0.31 mg/mL. The susceptibility of bacteria towards the plant extracts evaluated was species-dependent, with the susceptibility indices ranging from 0% for Escherichia coli to 72% for Pseudomonas aeruginosa. Conclusions: The results from this study show that extracts from these plants have significant antimicrobial activity, which corroborates their use in traditional medicine.
Keywords: bacteriostatic; bactericidal; broth microdilution; extraction; fungistatic; fungicidal; Diplazium esculentum; Sechium edule; S. muricatum